COMPARATIVE STUDY ON ACCOUNTING MODELS "CASH" AND "ACCRUAL" - DĂNESCU, Tatiana; RUS, Luminița (Annales Universitatis Apulensis Series Oeconomica, 2013)
Accounting, as a source of information, can recognize the economic transactions taking into account the time of payment or receipt thereof, as soon as they occur. There are two basic models of accounting: accrual basis and cash basis. In the cash accounting method the transactions are recorded only when cash is received or paid, shall not make the difference between the purchase of an asset and the payment of expenditure – both of which are considered "payments". Accrual accounting achieves this distinction, as recognized accounting transactions as soon as they occur. At the same time, accrual accounting method ensure accurate submission of transactions, but in order to determine cash flow is necessary to apply cash accounting method. In the cash basis, revenues and expenses are reported in the period in which the payment is made or the income is received, whereas, and on the basis of accrual-based accounting method, income is expressing the effect achieved with the effort called expenses. In order to research the opportunities of information provided by the two accounting models in this study – by applying a methodology of research subscribed to the constructivist current and based on a vast practical experiences in accounting activities that apply both models of accounting - we achieved a SWOT analysis with exposing the strengths and weaknesses of the two accounting models highlighting the convergence and divergence between them.